Different Manifestations in Familial Isolated Left Ventricular Non-compaction: Two Case Reports and Literature Review - Al Hussein, Hamida; Al Hussein, Hussam; Stroe, Valentin; Harpa, Marius; Ghiragosian, Claudiu; Goia, Cristina Maria; Opris, Carmen Elena; Suciu, Horatiu (Frontiers in Pediatrics, 2020)
Left ventricular non-compaction (LVNC) is a form of cardiomyopathy characterized by prominent trabeculae and deep intertrabecular recesses which form a distinct “non-compacted” layer in the myocardium. It results from intrauterine arrest of the compaction process of the left ventricular myocardium. Clinical manifestations vary from asymptomatic to heart failure (HF), arrhythmias or thromboembolic events. We present a case of mother and son diagnosed with isolated LVNC (ILVNC). A 4-year-old male patient, diagnosed at 3 months with ILVNC and NYHA functional class IV HF, was admitted to the Emergency Institute for Cardiovascular Diseases and Transplantation of Targu Mures, Romania, for cardiologic reevaluation and diagnosis confirmation. ILVNC was confirmed using echocardiography, revealing a non-compaction to compaction (NC/C) ratio of > 2.7. His evolution was stationary until the age of 8 years, when severe pneumonia caused hemodynamic decompensation, and he was listed for heart transplantation (HT). The patient underwent HT at the age of 11 years with favorable postoperative outcome. Meanwhile, a 22-year-old female patient, mother of the aforementioned patient, was also admitted to our institute due to severe fatigue, dyspnea and recurrent palpitations with multiple implantable cardioverter defibrillator (ICD) shock delivery. Extensive medical history revealed that a presumptive ILVNC diagnosis was established when she was 11 years old. She was asymptomatic until 18 years old, when 3 months post-partum, she developed NYHA functional class III HF, and subsequently underwent ICD implantation. Her diagnosis was confirmed using multi-detector computed tomography angiography, which revealed a NC/C ratio of > 3.3. ICD adjustments were carried out with a favorable evolution under chronic drug therapy. The last evaluation, at 27 years old, revealed that she was in NYHA functional class II HF. In conclusion, ILVNC, even when familial, can present different clinical pictures and therefore requires different medical approaches.